2018
DOI: 10.1021/acsabm.8b00071
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Based Highly Efficient Theranostic Nanoplatform for Two-Photon Bioimaging and Two-Photon Excited Photodynamic Therapy of Multiple Drug Resistance Bacteria

Abstract: Near-infrared (NIR) light between 700 and 2500 nm, which is in the range of the first, second, and third biological windows, has the capability to penetrate biological tissues and blood, which provides a huge advantages of higher penetration depth. However, because of the lack of available biocompatible single photon probes in NIR window, there is an urgent need for new theranostic material, which could be used for two-photon bioimaging as well as for two-photon photodynamic therapy (PDT) in biological window… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
110
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(114 citation statements)
references
References 51 publications
(156 reference statements)
4
110
0
Order By: Relevance
“… 45 54 Experimental details have been reported before and are discussed in the Supporting Information . 47 , 55 , 58 60 , 68 71 In brief, for the measurement, we used an 80 MHz Ti-sapphire laser as an excitation source with 100 fs pulse width. 47 , 55 , 58 60 We used an optical parametric amplifier to generate 800 nm excitation wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 45 54 Experimental details have been reported before and are discussed in the Supporting Information . 47 , 55 , 58 60 , 68 71 In brief, for the measurement, we used an 80 MHz Ti-sapphire laser as an excitation source with 100 fs pulse width. 47 , 55 , 58 60 We used an optical parametric amplifier to generate 800 nm excitation wavelength.…”
Section: Resultsmentioning
confidence: 99%
“… 47 , 55 , 58 60 , 68 71 In brief, for the measurement, we used an 80 MHz Ti-sapphire laser as an excitation source with 100 fs pulse width. 47 , 55 , 58 60 We used an optical parametric amplifier to generate 800 nm excitation wavelength. 3 , 47 , 55 , 58 , 60 The laser beam was focused down to a radius of ∼30 μm on the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[110][111][112][113] Two-photon absorption of ligand-protected metal NCs shows a nonlinear optical property that is attractive for applications such as biological imaging and PDT. 114 Vangara et al demonstrated twophoton PDT under 860 nm NIR excitation for multiple drug resistance bacteria (MDRB) using a nanocomposite of a-lipoic acid stabilized Au NCs and graphene quantum dots (GQDs) (Au NCs-GQDs nanocomposite), 115 where the GQDs with high NIR absorption act as two-photon donor-chromophores, while the Au NCs act as acceptors. Due to the FRET process between the Au NCs and the GQDs, the 1 O 2 generation capability of Au NCs-GQD nanocomposite enhanced tremendously, which was higher than that of rose bengal, which is an efficient organic photosensitizer ( 1 O 2 quantum yield of rose bengal, F RB ¼ 0.75) (Fig.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…Antibiotic resistant bacteria, which are a nightmare for medical treatment, are responsible for more than a million deaths in the world every year. [25][26][27][28][29][30] As per the Center for Disease Control and Prevention (CDC), antibiotic resistance is one of the biggest public health challenges in the 21 st century. 26 As a result, there is a huge urgency in nding rapid and costeffective assays which will have the capability for rapid and accurate determination of the appropriate antibiotic for an infection in a timely manner.…”
Section: Introductionmentioning
confidence: 99%